God and the Universe in the Vedantic Theology of Ramanuja - ., JOD (Journal of Dharma, 1980)
Eric J. Lott, God and the Universe in the Vedantic Theology of Ramanuja, Madras, Rarnanuja Research Society, 1976, pp. xxi + 247.